Effects of Chocolates Using Low Calorie Cocoa Butter Substitutes on Rat’s Plasma Profile and Determination of Sn-1,3 Position - B.. Ros-Haniza; S. Mamot (Universitas Gadjah Mada, 2013)
The present study sought to determine the effectiveness of newly developed low calorie chocolate using modified fat through enzymatic interesterification process as cocoa butter substitute of male Sprague Dawley rats (n = 35) compared to cocoa butter as control. Body weight gains did not differ significantly (p>0.05) in all the test groups fed with chocolates which were using different types of fats. Triacylglycerol and cholesterol test showed no significant difference (p>0.05) for all treatment samples. in this study, a pancreatic lipase hydrolysis was performed to determine the fatty acid composition of the sn-2 position of the structure lipids.